Pengembangan Media Pembelajaran pada Mata Pelajaran IPA Kelas IV SD Negeri 48 Oku : Development of Learning Media for Science Subjects in Grade IV of SD Negeri 48 Oku - Faradilah Chairunnisa; Yamanto Isa; Arief Qosim (ITScience (Information Technology and Science), 2025)
This study aims to develop PowerPoint-based learning media for the fourth-grade science subject of SD Negeri 48 OKU. The type of research used is development research with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data collection technique was done through a questionnaire, while the data analysis used the percentage method. The results of the expert review showed that the material expert evaluation of 6 instrument items obtained an average percentage of 77% with good information, media experts from 6 instrument items obtained an average percentage of 79% with good information, and design experts from 4 instrument items obtained an average percentage of 76% with good information. Furthermore, the individual trial (one-to-one) results showed a percentage of 78.7% with good information, small group tests of 80.2% with good information, and field tests obtained 82.7% with good information. Based on these results, this PowerPoint-based learning media product is declared suitable for science learning in the fourth grade of SD Negeri 48 OKU. The novelty of this research lies in developing PowerPoint-based learning media specifically designed for the local context of elementary schools at SD Negeri 48 OKU, by integrating science materials according to student needs and the characteristics of 21st-century learning.